Exploring the influence of technology affordance on purchase intention through immersion in Shopee live streaming shopping in Indonesia - Salsabila, Shatifa; Patrisia, Dina (Universitas Negeri Padang, 2024)
This research focuses on viewers purchasing intentions through Shopee live streaming shopping. The aim of this research is to find out how visibility, metavoicing, and guidance shopping on affordance technology can influence purchase intention on Shopee live streaming shopping which is mediated by the immersion variable. The sample used was 241 respondents. Data processing was carried out using SmartPLS and collected through an online questionnaire. The research results show that (1) Visibility has a negative and significant effect on immersion. (2) Metavoicing has a positive and significant effect on immersion. (3) Guidance Shopping has a positive and significant effect on immersion. (4) Immersion has a positive and significant effect on purchase intention. (5) Visibility has a negative and significant effect on purchase intention with immersion as mediation, (6) Metavoicing has a positive and significant effect on purchase intention with immersion as mediation. (7) Guidance Shopping has a positive and significant effect on purchase intention with immersion as mediation.